Anion exchange membrane, preparation method and application thereof and electrolysis device

By grafting the side chains containing fluorine and phenyl groups on the polymer main chain of the anion exchange membrane, the problem of insufficient conductivity and chemical stability of the anion exchange membrane is solved, and higher conductivity and better Chemical stability.

CN119465288AActive Publication Date: 2025-02-18HYDROGEN & YUANTAI (CHANGZHOU) NEW MATERIALS TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411563851.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-18
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing anion exchange membranes have problems such as poor ion conductivity, insufficient chemical stability, and poor compatibility between the membrane and the electrode interface.

Method used

The polymer backbone is grafted and modified by side chains containing fluorine and phenyl groups to improve the conductivity and chemical stability of the anion exchange membrane.

Benefits of technology

The conductivity and chemical stability of the anion exchange membrane are improved, and the excessive expansion and performance of the membrane are suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465288A_ABST
    Figure CN119465288A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrolysis, and provides an anion exchange membrane, a preparation method and application thereof and an electrolysis device, the anion exchange membrane comprises a polymer main chain, the polymer main chain is grafted with a plurality of side chains, and the side chains contain fluorine groups and phenyl groups. The anion exchange membrane is high in conductivity and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrolysis technology, and in particular to an anion exchange membrane and a preparation method, application and electrolysis device thereof. Background Art

[0002] Hydrogen production by water electrolysis has become an important method of hydrogen production due to its simple principle and high energy efficiency. Among them, the key to water electrolysis lies in the electrolyte materials used in the electrolyzer, especially the performance of the membrane material, which directly affects the electrolysis efficiency and hydrogen production. Anion exchange membrane (AEM) type electrolyzer is a new type of electrolyzer technology that has developed rapidly in recent years. It has the advantages of low cost of traditional alkaline electrolyzers and high electrolysis efficiency of proton exchange membrane type electrolyzers. Quaternary ammonium salt anion exchange membrane and polyaryl piperidine anion exchange membrane are used in traditional technologies. Quaternary ammonium salt anion exchange membrane has problems such as poor ion conductivity, insufficient chemical stability and poor compatibility between the membrane and the electrode interface; the ion conductivity and alkali resistance of polyaryl piperidine anion exchange membrane still need to be improved. Therefore, how to improve the conductivity and stability of anion exchange membrane has become a technical problem that urgently needs to be solved. Summary of the invention

[0003] Based on this, an embodiment of the present application provides an anion exchange membrane with high conductivity and good stability, and a preparation method, application and electrolysis device thereof.

[0004] In a first aspect, the present application provides an anion exchange membrane, which includes a polymer main chain, a plurality of side chains grafted onto the polymer main chain, and the side chains contain fluorine groups and phenyl groups.

[0005] In some embodiments, the polymer backbone includes at least one of a polyarylpiperidine polymer, a polyarylisatin polymer, and a polybenzimidazole polymer.

[0006] In some embodiments, the side chain includes at least one of a 2,4,5-trifluorobenzyl group, a 2,3,6-trifluorobenzyl group, a 3,4,5-trifluorobenzyl group, a 4-fluoroethylphenyl group, a 3,4-difluorobenzyl group, a 2,4-difluorobenzyl group, and a 2,6-difluorobenzyl group.

[0007] In some embodiments, the mass ratio of the polymer main chain to the side chain is 1:(0.07-0.3).

[0008] In a second aspect, the present application provides a method for preparing an anion exchange membrane, the preparation method comprising:

[0009] A polymer main chain, a grafting agent and an acid binding agent are mixed to obtain a mixed solution, wherein the grafting agent is grafted onto the polymer main chain to form a side chain containing a fluorine group and a phenyl group, thereby preparing a polymer material;

[0010] Dissolving the polymer material to form a casting solution, and applying the casting solution to obtain a prefabricated membrane;

[0011] The prefabricated membrane is subjected to ion exchange treatment to prepare the anion exchange membrane.

[0012] In some embodiments, the mass ratio of the polymer main chain to the grafting agent is 1:(0.07-0.3).

[0013] In some embodiments, the mass ratio of the polymer main chain to the acid binding agent is 1:(0.5~1).

[0014] In some embodiments, the grafting agent includes at least one of 2,4,5-trifluorobenzyl bromide, 2,3,6-trifluorobenzyl bromide, 3,4,5-trifluorobenzyl bromide, 4-fluorobromoethylbenzene, 3,4-difluorobenzyl bromide, 2,4-difluorobenzyl bromide, and 2,6-difluorobenzyl bromide.

[0015] In some embodiments, the acid binding agent includes at least one of potassium carbonate, sodium hydride, sodium bicarbonate, trimethylamine and sodium carbonate.

[0016] In some embodiments, the mass percentage concentration of the polymer material in the casting solution is 5% to 25%.

[0017] In some embodiments, the ion exchange treatment comprises:

[0018] The prefabricated membrane is subjected to ion exchange treatment using an alkaline solution.

[0019] Optionally, the alkaline compound contained in the alkaline solution includes at least one of potassium hydroxide, sodium hydroxide and calcium hydroxide.

[0020] In some embodiments, after the grafting agent is grafted onto the polymer main chain, the preparation method further comprises: adding a halogenated alkane to perform a quaternization reaction on the polymer main chain.

[0021] Optionally, the mass ratio of the polymer main chain to the halogenated alkane is 1:(0.6~1).

[0022] Optionally, the halogenated alkane includes at least one of methyl iodide, ethyl iodide and 2-iodopropane.

[0023] In some embodiments, the method for preparing the polymer backbone comprises:

[0024] mixing an aromatic monomer and a ketone monomer to obtain a first solution;

[0025] The first solution and the acidic catalyst are mixed to prepare a polymer main chain.

[0026] In some embodiments, the molar ratio of the aromatic monomer to the ketone monomer is 1-1.2:1.

[0027] In some embodiments, the aromatic monomer includes at least one of p-terphenyl, m-terphenyl, biphenyl, bibenzyl, and 9,9′-diphenylfluorene.

[0028] In some embodiments, the ketone monomer includes at least one of N-methyl-4-piperidone, isatin, 3-quininone, 1,1,1-trifluoroacetone, and 2,2,2-trifluoroacetophenone.

[0029] In some embodiments, the acidic catalyst includes at least one of trifluoroacetic acid, trifluoromethanesulfonic acid, perfluoropropionic acid, pentafluoroethanesulfonic acid, and heptafluorobutyric acid.

[0030] Optionally, the acidic catalyst comprises trifluoroacetic acid and trifluoromethanesulfonic acid. Further optionally, the molar ratio of the trifluoroacetic acid to the ketone monomer is 1-1.5:1; the molar ratio of the trifluoromethanesulfonic acid to the ketone monomer is 9-12:1.

[0031] In a third aspect, the present application provides a use of the anion exchange membrane as described in the first aspect in preparing an electrolysis device.

[0032] In a fourth aspect, the present application provides an electrolysis device, comprising the anion exchange membrane as described in the first aspect and / or an anion exchange membrane prepared by the method for preparing an anion exchange membrane as described in the second aspect.

[0033] Compared with the traditional technology, this application has at least the following beneficial effects:

[0034] The present invention adopts a side chain containing a fluorine group and a phenyl group to graft and modify the polymer main chain. The side chain is large in size and highly hydrophobic, which can promote the aggregation of hydrophilic cationic groups, thereby promoting microphase separation, facilitating the rapid movement of ions, and improving the conductivity of the anion exchange membrane. In addition, the introduction of the hydrophobic large-volume side chain of the present invention helps to inhibit the excessive expansion and performance degradation of the anion exchange membrane during use, and improves the chemical stability of the membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 FT-IR spectra of the polymer backbones prepared in Example 3 and Comparative Example 1 of the present application;

[0036] Figure 2The contact angle diagram of the anion exchange membrane prepared in Example 3 and Comparative Example 1 of the present application and water;

[0037] Figure 3 This is a comparison chart of the mechanical strength of the anion exchange membranes prepared in Examples 1-3 of the present application and Comparative Example 1;

[0038] Figure 4 Polarization curves of alkaline water electrolysis by anion exchange membrane in Example 3 and Comparative Example 1 of the present application;

[0039] Figure 5 This is a comparison diagram of the microscopic morphology of the anion exchange membrane in Example 3 of the present application and Comparative Example 1. DETAILED DESCRIPTION

[0040] Below in conjunction with the embodiments and examples, the present application is further described in detail. These embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0042] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0043] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0044] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0045] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0046] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0047] In traditional technology, in order to improve the ion conductivity of anion exchange membranes, a side chain structure with multiple hydrophilic cations is introduced into the polymer main chain to increase the local ion group density, thereby promoting microphase separation and improving ion conductivity. However, a higher ion exchange capacity will greatly increase the water absorption and swelling rate of the anion exchange membrane, causing the dimensional stability of the membrane to decrease, thereby affecting the overall service life of the anion exchange membrane.

[0048] In a first aspect, the present application provides an anion exchange membrane, which includes a polymer main chain, a plurality of side chains grafted onto the polymer main chain, and the side chains contain fluorine groups and phenyl groups.

[0049] The present invention adopts a side chain containing a fluorine group and a phenyl group to graft and modify the polymer main chain. The side chain is large in size and highly hydrophobic, which can promote the aggregation of hydrophilic cationic groups, thereby promoting microphase separation, facilitating the rapid movement of ions, and improving the conductivity of the anion exchange membrane. In addition, the introduction of the hydrophobic large-volume side chain of the present invention helps to inhibit the excessive expansion and performance degradation of the anion exchange membrane during use, and improves the chemical stability of the membrane.

[0050] In some embodiments, the polymer backbone comprises at least one of a polyaryl piperidine polymer, a polyaryl isatin polymer and a polybenzimidazole polymer. Optionally, the polymer backbone comprises a quaternized polyaryl piperidine polymer. The present application adopts a quaternized polyaryl piperidine polymer as the polymer backbone, and cooperates with a side chain containing a fluorine group and a phenyl group, has good swelling resistance and good microphase separation, thereby being able to improve the ionic conductivity and alkali resistance stability of the anion exchange membrane.

[0051] It is understood that in the present application, the polymer main chain can also be modified by grafting other modifying groups to improve the performance of the anion exchange membrane. For example, at least part of the piperidine groups in the polymer main chain are quaternized with methyl iodide.

[0052] In some embodiments, the side chain includes at least one of a 2,4,5-trifluorobenzyl group, a 2,3,6-trifluorobenzyl group, a 3,4,5-trifluorobenzyl group, a 4-fluoroethylphenyl group, a 3,4-difluorobenzyl group, a 2,4-difluorobenzyl group, and a 2,6-difluorobenzyl group.

[0053] In some embodiments, the mass ratio of the polymer main chain to the side chain is 1:(0.07-0.3), for example, it can be 1:0.07, 1:0.10, 1:0.13, 1:0.16, 1:0.19, 1:0.22, 1:0.25, 1:0.28 or 1:0.0.30.

[0054] The second aspect of the present application provides a method for preparing an anion exchange membrane, the preparation method comprising:

[0055] A polymer main chain, a grafting agent and an acid binding agent are mixed to obtain a mixed solution, wherein the grafting agent is grafted onto the polymer main chain to form a side chain containing a fluorine group and a phenyl group, thereby preparing a polymer material;

[0056] Dissolving the polymer material to form a casting solution, and applying the casting solution to obtain a prefabricated membrane;

[0057] The prefabricated membrane is subjected to ion exchange treatment to prepare the anion exchange membrane.

[0058] The present application prepares an anion exchange membrane as described above, grafts side chains onto the polymer main chain, and the preparation method is simple, and the prepared anion exchange membrane has high ion conductivity and good dimensional stability. Specifically, the present application adopts side chains containing fluorine groups and phenyl groups to graft and modify the polymer main chain. The side chains are large in volume and highly hydrophobic, which can promote the aggregation of hydrophilic cationic groups, thereby promoting microphase separation, facilitating the rapid movement of ions, and improving the conductivity of the anion exchange membrane. In addition, the introduction of the hydrophobic bulky side chains of the present application helps to suppress the excessive expansion and performance degradation of the anion exchange membrane during use, and improves the chemical stability of the membrane.

[0059] It is understood that in the present application, the polymer main chain can also be modified by grafting other modifying groups to improve the performance of the anion exchange membrane, for example, partially iodomethane the polymer main chain.

[0060] In some embodiments, the mass ratio of the polymer backbone to the grafting agent is 1:(0.07-0.3), for example, 1:0.07, 1:0.10, 1:0.13, 1:0.16, 1:0.19, 1:0.22, 1:0.25, 1:0.28 or 1:0.0.30.

[0061] In some embodiments, the mass ratio of the polymer backbone to the acid binding agent is 1:(0.5-1), for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1.0.

[0062] In some embodiments, the grafting agent includes at least one of 2,4,5-trifluorobenzyl bromide, 2,3,6-trifluorobenzyl bromide, 3,4,5-trifluorobenzyl bromide, 4-fluorobromoethylbenzene, 3,4-difluorobenzyl bromide, 2,4-difluorobenzyl bromide, and 2,6-difluorobenzyl bromide.

[0063] In some embodiments, the acid binding agent includes at least one of potassium carbonate, sodium hydride, sodium bicarbonate, trimethylamine and sodium carbonate.

[0064] In some embodiments, the mass percentage concentration of the polymer material in the casting solution is 5% to 25%, for example, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24% or 25%.

[0065] In some embodiments, the ion exchange treatment comprises:

[0066] The prefabricated membrane is subjected to ion exchange treatment using an alkaline solution.

[0067] Optionally, the alkaline compound contained in the alkaline solution includes at least one of potassium hydroxide, sodium hydroxide and calcium hydroxide.

[0068] In some embodiments, after the grafting agent is grafted onto the polymer main chain, the preparation method further comprises: adding a halogenated alkane to perform a quaternization reaction on the polymer main chain.

[0069] Optionally, the mass ratio of the polymer main chain to the halogenated alkane is 1:(0.6-1), for example, it can be 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1.0.

[0070] Optionally, the halogenated alkane includes at least one of methyl iodide, ethyl iodide and 2-iodopropane.

[0071] In some embodiments, the preparation process of the polymer material comprises the following steps:

[0072] A grafting agent and an acid binding agent are added to a solution containing a polymer main chain to obtain a mixed solution. After a period of reaction, a halogenated alkane is added to the mixed solution. After a quaternization reaction, a first precipitant is added. The precipitate is washed and vacuum dried to obtain the polymer material.

[0073] In some embodiments, the solvent contained in the solution containing the polymer backbone includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0074] In some embodiments, a grafting agent and an acid binding agent are added to a solution containing a polymer main chain to obtain a mixed solution, and the reaction time is 24 hours to 48 hours.

[0075] In some embodiments, the quaternization temperature is 30° C. to 40° C., the environment is protected from light, and the time is 24 h to 48 h.

[0076] In some embodiments, the first precipitating agent comprises at least one of ethyl acetate, acetone, and diethyl ether.

[0077] In some embodiments, the vacuum drying temperature of the polymer material is 60° C. to 100° C., and the time is 24 h to 36 h.

[0078] In some embodiments, the method for preparing the polymer backbone comprises:

[0079] mixing an aromatic monomer and a ketone monomer to obtain a first solution;

[0080] The first solution and the acidic catalyst are mixed to prepare a polymer main chain.

[0081] In some embodiments, the molar ratio of the aromatic monomer to the ketone monomer is 1-1.2:1, for example, 1.05:1, 1.10:1, 1.15:1 or 1.20:1.

[0082] In some embodiments, the aromatic monomer includes at least one of p-terphenyl, m-terphenyl, biphenyl, bibenzyl, and 9,9′-diphenylfluorene.

[0083] In some embodiments, the ketone monomer includes at least one of N-methyl-4-piperidone, isatin, 3-quinindone, 1,1,1-trifluoroacetone, and 2,2,2-trifluoroacetophenone.

[0084] In some embodiments, the acidic catalyst includes at least one of trifluoroacetic acid, trifluoromethanesulfonic acid, perfluoropropionic acid, pentafluoroethanesulfonic acid, and heptafluorobutyric acid.

[0085] Optionally, the acidic catalyst comprises trifluoroacetic acid and trifluoromethanesulfonic acid. Further optionally, the molar ratio of the trifluoroacetic acid to the ketone monomer is 1-1.5:1; the molar ratio of the trifluoromethanesulfonic acid to the ketone monomer is 9-12:1.

[0086] In some embodiments, the solvent contained in the first solution includes at least one of dichloromethane, trifluoroacetic acid, and trifluoromethanesulfonic acid.

[0087] In some embodiments, after the first solution and the acidic catalyst are mixed, a second precipitant is added after a period of reaction to precipitate a polymer backbone. Optionally, the polymer backbone is also washed and vacuum dried. Optionally, the reaction time is 6h~8h. Optionally, the second precipitant includes at least one of anhydrous methanol, anhydrous ethanol, potassium hydroxide solution and sodium hydroxide solution. Optionally, the vacuum drying temperature is 30°C~100°C, and the time is 24h~36h.

[0088] Exemplarily, a method for preparing the above anion exchange membrane is provided, comprising the following steps:

[0089] (1) Polymer main chain

[0090] The aromatic monomer and the ketone monomer are mixed in a molar ratio of 1 to 1.2:1 to obtain a first solution; an acidic catalyst is added to the first solution, and a second precipitant is added after reacting for 6 to 8 hours, and the precipitate is washed to neutrality, and then vacuum dried at 30°C to 100°C for 24 hours to 36 hours to obtain a polymer main chain.

[0091] (2) Prefabricated membrane

[0092] The polymer main chain is dissolved, and then a grafting agent and an acid binding agent are added, and the reaction is carried out for 24 hours to 48 hours; then a halogenated alkane is added, and a quaternization reaction is carried out at 30° C. to 40° C. in the dark for 24 hours to 48 hours, and then a first precipitant is added, and the precipitate is washed with deionized water for multiple times, and then vacuum dried at 60° C. to 100° C. for 24 hours to 36 hours to obtain a polymer material;

[0093] The polymer material is dissolved to form a solution with a mass percentage concentration of 5% to 25% to obtain a casting solution, the casting solution is coated to form a film, and the prefabricated film is obtained after drying at 60° C. to 100° C. for 24 h to 36 h.

[0094] (3) Ion treatment

[0095] The prefabricated membrane is subjected to ion exchange treatment using an alkaline solution to prepare the anion exchange membrane.

[0096] The third aspect of the present application provides a use of the anion exchange membrane as described in the first aspect in the preparation of an electrolysis device.

[0097] A fourth aspect of the present application provides an electrolysis device, which comprises the anion exchange membrane as described in the first aspect and / or the anion exchange membrane prepared by the method for preparing the anion exchange membrane as described in the second aspect.

[0098] In some embodiments, the electrolysis device includes a cathode, an anode, an anion exchange membrane, and an electrolytic cell injected with an electrolyte. The cathode, anode, and anion exchange membrane are respectively disposed in the electrolytic cell, and the anion exchange membrane is disposed between the cathode and the anode.

[0099] The embodiments of the present application will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance provided in the present application, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0100] Example 1

[0101] (1) Polymer main chain

[0102] In an ice bath, 4.6 g of terphenyl and 2.5 mL of N-methyl-4-piperidone were added to 10 mL of dichloromethane and mixed; then, a mixed solution of 1.5 mL of trifluoroacetic acid and 16 mL of trifluoromethanesulfonic acid was added dropwise, and the reaction was continued for 6 hours. The mixture was poured into anhydrous methanol and precipitated to obtain a polymer main chain; finally, the polymer main chain was repeatedly washed with deionized water until the pH was neutral, and vacuum dried at 60°C for 24 hours to obtain a polymer main chain.

[0103] (2) Prefabricated membrane

[0104] Weigh 1 g of the polymer main chain obtained in step (1) and dissolve it in 10 mL of NMP and 10 mL of DMSO. Then, add 0.04 mL of 2,4,5-trifluorobenzyl bromide to the reaction system, and add 0.62 g of potassium carbonate as an acid binding agent to react for 24 hours. Then, add 0.38 mL of iodomethane to the reaction system and react at 30°C in the dark for 24 hours. Finally, pour the reaction solution into ethyl acetate for precipitation, wash with deionized water, and then vacuum dry at 80°C for 24 hours to obtain a polymer material.

[0105] 0.5 g of the above polymer material was weighed and dissolved in 10 mL of DMSO. After centrifugation to remove impurities, the casting solution was cast on a glass plate and dried at 60° C. for 24 h to form a film to obtain a prefabricated membrane.

[0106] (3) Ion treatment

[0107] The prefabricated membrane is subjected to ion exchange treatment using a 1 mol / L KOH solution to prepare the anion exchange membrane.

[0108] Example 2

[0109] (1) Polymer main chain

[0110] In an ice bath, 4.6 g of terphenyl and 2.5 mL of N-methyl-4-piperidone were added to 10 mL of dichloromethane and mixed; then, a mixed solution of 1.8 mL of trifluoroacetic acid and 18 mL of trifluoromethanesulfonic acid was added dropwise, and the reaction was continued for 7 hours. The mixture was poured into anhydrous methanol and precipitated to obtain a polymer main chain; finally, the polymer main chain was repeatedly washed with deionized water until the pH was neutral, and vacuum dried at 70°C for 36 hours to obtain a polymer main chain.

[0111] (2) Prefabricated membrane

[0112] Weigh 1 g of the polymer main chain obtained in step (1) and dissolve it in 10 mL of NMP and 10 mL of DMSO. Then, add 0.04 mL of 2,4,5-trifluorobenzyl bromide to the reaction system, and add 0.65 g of potassium carbonate as an acid binding agent to react for 36 hours. Then, add 0.4 mL of iodomethane to the reaction system and react at 35°C in the dark for 36 hours. Finally, pour the reaction solution into ethyl acetate for precipitation, wash with deionized water, and vacuum dry at 80°C for 24 hours to obtain a polymer material.

[0113] 0.5 g of the above polymer material was weighed and dissolved in 10 mL of DMSO. After centrifugation to remove impurities, the casting solution was cast on a glass plate and dried at 70° C. for 36 h to form a film to obtain a prefabricated membrane.

[0114] (3) Ion treatment

[0115] The prefabricated membrane is subjected to ion exchange treatment using a 1 mol / L KOH solution to prepare the anion exchange membrane.

[0116] Example 3

[0117] (1) Polymer main chain

[0118] In an ice bath, 4.6 g of terphenyl and 2.5 mL of N-methyl-4-piperidone were added to 10 mL of dichloromethane and mixed; then, a mixed solution of 2 mL of trifluoroacetic acid and 20 mL of trifluoromethanesulfonic acid was added dropwise, and the reaction was continued for 8 hours. The polymer main chain was poured into anhydrous methanol for precipitation; finally, the polymer main chain was repeatedly washed with deionized water until the pH was neutral, and vacuum dried at 100°C for 36 hours to obtain the polymer main chain.

[0119] (2) Prefabricated membrane

[0120] 1 g of the polymer main chain obtained in step (1) was weighed and dissolved in 10 mL of NMP and 10 mL of DMSO. Then, 0.08 mL of 2,4,5-trifluorobenzyl bromide was added to the reaction system, and 0.68 g of potassium carbonate was added as an acid binding agent to react for 36 h. Then, 0.6 mL of iodomethane was added to the reaction system, and the reaction was carried out at 40 ° C in the dark for 30 h. Finally, the reaction solution was poured into ether for precipitation, washed with deionized water, and vacuum dried at 80 ° C for 24 h to obtain a polymer material, whose FT-IR spectrum is shown as follows: Figure 1 As shown;

[0121] 0.5 g of the above polymer material was weighed and dissolved in 10 mL of DMSO. After centrifugation to remove impurities, the casting solution was cast on a glass plate and dried at 100° C. for 30 h to form a film to obtain a prefabricated membrane.

[0122] (3) Ion treatment

[0123] The prefabricated membrane is subjected to ion exchange treatment using a 1 mol / L KOH solution to prepare the anion exchange membrane.

[0124] Example 4

[0125] An anion exchange membrane was prepared according to the method of Example 3, except that the mass ratio of the polymer main chain to the grafting agent was 1:0.02.

[0126] Example 5

[0127] An anion exchange membrane was prepared according to the method of Example 3, except that the mass ratio of the polymer main chain to the grafting agent was 1:0.5.

[0128] Comparative Example 1

[0129] (1) Polymer main chain

[0130] In an ice bath, 4.6 g of terphenyl and 2.5 mL of N-methyl-4-piperidone were added to 10 mL of dichloromethane and mixed; then, a mixed solution of 1.7 mL of trifluoroacetic acid and 17 mL of trifluoromethanesulfonic acid was added dropwise, and the reaction was continued for 6 hours. The polymer main chain was poured into anhydrous methanol for precipitation; finally, the polymer main chain was repeatedly washed with deionized water until the pH was neutral, and vacuum dried at 70°C for 24 hours to obtain the polymer main chain.

[0131] (2) Prefabricated membrane

[0132] 1 g of the polymer main chain obtained in step (1) was weighed and dissolved in 10 mL of NMP and 10 mL of DMSO, followed by adding 0.62 g of potassium carbonate as an acid binding agent to react for 24 h; then 0.6 mL of iodomethane was added to the reaction system, and the reaction was carried out at 35 ° C in the dark for 24 h; finally, the reaction solution was poured into ether for precipitation, washed with deionized water, and vacuum dried at 80 ° C for 24 h to obtain a polymer material, whose FT-IR spectrum is shown as follows Figure 1 As shown;

[0133] 0.5 g of the above polymer material was weighed and dissolved in 10 mL of DMSO. After centrifugation to remove impurities, the casting solution was cast on a glass plate and dried at 80° C. for 24 h to form a film to obtain a prefabricated membrane.

[0134] (3) Ion treatment

[0135] The prefabricated membrane is subjected to ion exchange treatment using a 1 mol / L KOH solution to prepare the anion exchange membrane.

[0136] Comparative Example 2

[0137] An anion exchange membrane was prepared according to the method of Example 3, except that the grafting agent was replaced with 0.06 mL of 2-iodo-1,1,1-trifluoroethane.

[0138] Comparative Example 3

[0139] An anion exchange membrane was prepared according to the method of Example 3, except that the grafting agent was replaced with 0.083 mL of β-bromophenylethane.

[0140] The anion exchange membranes prepared in the above examples and comparative examples were tested for performance, and the testing method included:

[0141] Impedance test: The p-EIS method was used to detect the impedance of the anion exchange membrane at room temperature (25°C) using an electrochemical workstation (gamry);

[0142] Conductivity: The resistance at room temperature (25°C) was measured by the p-EIS impedance method, and the conductivity of the membrane was calculated by the formula σ=L / RA, (R is the impedance value of the membrane, L is the thickness of the membrane, and A is the effective area of ​​the membrane);

[0143] Contact angle: The contact angle between anion exchange membrane and water was tested using a contact angle tester (JY-PHcAngleTester), where: Figure 2 The contact angle diagrams of Example 3 and Comparative Example 1 with water;

[0144] Mechanical strength: The tensile strength and elongation at break of the wet film were tested using a tensile machine (LABRD-V2.9). Figure 3 The figure is a comparison chart of mechanical strength of Example 1, Example 2, Example 3 and Comparative Example 1;

[0145] Current density: At 55°C, without cathode and anode catalysts, and at a voltage of 2V, the current density was tested using an electrolytic water test system. Figure 4 Graph showing the polarization curves of alkaline electrolyzed water in Example 3 and Comparative Example 1.

[0146] Microstructure characterization: The microstructure of the anion exchange membrane was measured using a transmission electron microscope (JEOL JEM-2000EX). The microstructure of the anion exchange membrane in Example 3 and Comparative Example 1 was compared. Figure 5 shown.

[0147] The test results are shown in Table 1.

[0148] Table 1

[0149]

[0150] From the above table we can see that:

[0151] (1) Compared with Examples 4-5, it can be seen that by controlling the amount of grafting agent added, the present application enables the anion exchange membrane to have higher ion conductivity, better tensile strength, and better water electrolysis performance. If the amount of grafting agent added is relatively low, the driving force of the hydrophobic side chain on the aggregation of the hydrophilic cationic groups may be insufficient, resulting in problems such as the inability to form ion clusters and the inability to improve ion conductivity. If the amount of grafting agent added is relatively high, the ion exchange capacity in the membrane may be greatly reduced, resulting in problems such as a reduced proportion of hydrophilic water areas and low ion conductivity.

[0152] (2) Compared with Comparative Examples 1, 2 and 3, it can be seen that Figure 5Compared with the micromorphology of Example 3 and the micromorphology of Comparative Example 1, Example 3 has more obvious microphase separation, lower impedance and higher ion conductivity. The present application grafts side chains containing F elements and phenyl groups. From the mechanical property data, it can be seen that as the amount of hydrophobic bulky side chains introduced increases, its mechanical properties are significantly improved. As the amount of hydrophobic bulky side chains introduced increases, its battery performance is improved, which shows that the introduction of hydrophobic bulky side chains promotes microphase separation in the membrane to a certain extent, improves conductivity, and thus improves battery performance.

[0153] In summary, the present application adopts a side chain containing a fluorine group and a phenyl group to graft and modify the polymer main chain. The side chain is large in size and highly hydrophobic, which can promote the aggregation of hydrophilic cationic groups, thereby promoting microphase separation, facilitating the rapid movement of ions, and improving the conductivity of the anion exchange membrane. In addition, the introduction of the hydrophobic bulky side chain of the present application helps to inhibit the excessive expansion and performance degradation of the anion exchange membrane during use, and improves the chemical stability of the membrane.

[0154] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0155] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the application. It should be noted that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An anion exchange membrane, characterized in that The anion exchange membrane comprises a polymer main chain, a plurality of side chains are grafted onto the polymer main chain, and the side chains contain fluorine groups and phenyl groups.

2. The anion exchange membrane according to claim 1, characterized in that The anion exchange membrane satisfies at least one of the following conditions: (1) The polymer main chain comprises at least one of a polyaryl piperidine polymer, a polyaryl isatin polymer and a polybenzimidazole polymer; (2) the side chain includes at least one of a 2,4,5-trifluorobenzyl group, a 2,3,6-trifluorobenzyl group, a 3,4,5-trifluorobenzyl group, a 4-fluoroethylphenyl group, a 3,4-difluorobenzyl group, a 2,4-difluorobenzyl group and a 2,6-difluorobenzyl group; (3) The mass ratio of the polymer main chain to the side chain is 1:(0.07~0.3).

3. A method for preparing an anion exchange membrane, characterized in that: The preparation method comprises: A polymer main chain, a grafting agent and an acid binding agent are mixed to obtain a mixed solution, wherein the grafting agent is grafted onto the polymer main chain to form a side chain containing a fluorine group and a phenyl group, thereby preparing a polymer material; Dissolving the polymer material to form a casting solution, and applying the casting solution to obtain a prefabricated membrane; The prefabricated membrane is subjected to ion exchange treatment to prepare the anion exchange membrane.

4. The method for preparing an anion exchange membrane according to claim 3, characterized in that: The method for preparing the anion exchange membrane satisfies at least one of the following conditions: (1) The mass ratio of the polymer main chain to the grafting agent is 1:(0.07-0.3); (2) The mass ratio of the polymer main chain to the acid binding agent is 1:(0.5~1); (3) the grafting agent includes at least one of 2,4,5-trifluorobenzyl bromide, 2,3,6-trifluorobenzyl bromide, 3,4,5-trifluorobenzyl bromide, 4-fluorobromoethylbenzene, 3,4-difluorobenzyl bromide, 2,4-difluorobenzyl bromide and 2,6-difluorobenzyl bromide; (4) The acid binding agent includes at least one of potassium carbonate, sodium hydride, sodium bicarbonate, trimethylamine and sodium carbonate; (5) The mass percentage concentration of the polymer material in the casting solution is 5% to 25%.

5. The method for preparing an anion exchange membrane according to claim 3, characterized in that: The ion exchange treatment comprises: Performing ion exchange treatment on the prefabricated membrane using an alkaline solution; Optionally, the alkaline compound contained in the alkaline solution includes at least one of potassium hydroxide, sodium hydroxide and calcium hydroxide.

6. The method for preparing an anion exchange membrane according to claim 3, characterized in that: After the grafting agent is grafted onto the polymer main chain, the preparation method further comprises: adding halogenated alkane to carry out quaternization reaction on the polymer main chain; Optionally, the mass ratio of the polymer backbone to the halogenated alkane is 1:(0.6~1); Optionally, the halogenated alkane includes at least one of methyl iodide, ethyl iodide and 2-iodopropane.

7. The method for preparing an anion exchange membrane according to any one of claims 3 to 6, characterized in that: The preparation method of the polymer main chain comprises: mixing an aromatic monomer and a ketone monomer to obtain a first solution; The first solution and the acidic catalyst are mixed to prepare a polymer main chain.

8. The method for preparing an anion exchange membrane according to claim 7, characterized in that: The preparation method of the polymer backbone meets at least one of the following conditions: (1) The molar ratio of the aromatic monomer to the ketone monomer is 1 to 1.2:1; (2) the aromatic monomer includes at least one of p-terphenyl, m-terphenyl, biphenyl, bibenzyl and 9,9'-diphenylfluorene; (3) the ketone monomer includes at least one of N-methyl-4-piperidone, isatin, 3-quininone, 1,1,1-trifluoroacetone and 2,2,2-trifluoroacetophenone; (4) The acidic catalyst includes at least one of trifluoroacetic acid, trifluoromethanesulfonic acid, perfluoropropionic acid, pentafluoroethanesulfonic acid and heptafluorobutyric acid; Optionally, the acidic catalyst includes trifluoroacetic acid and trifluoromethanesulfonic acid; further optionally, the molar ratio of the trifluoroacetic acid to the ketone monomer is 1-1.5:1; the molar ratio of the trifluoromethanesulfonic acid to the ketone monomer is 9-12:

1.

9. Use of the anion exchange membrane according to claim 1 or 2 in preparing an electrolysis device.

10. An electrolysis device, characterized in that: The electrolysis device comprises the anion exchange membrane according to claim 1 or 2 and / or an anion exchange membrane prepared by the method for preparing an anion exchange membrane according to any one of claims 3-8.

Citation Information

Patent Citations

  • Physical crosslinking type polymer anion exchange membrane and preparation method thereof

    CN114539578A

  • Anion-solvated polymer membranes

    CN115516014A

  • Pentafluorophenyl aromatic polymer with side chain containing sulfydryl nitrogen heterocyclic ring, preparation method and application of pentafluorophenyl aromatic polymer, and preparation method of high-temperature proton exchange membrane

    CN115873191A

  • Alkaline electrolyte and preparation method and application thereof

    CN115911479A

  • Perfluoro side chain grafted anion exchange membrane and preparation method thereof

    CN116845307A